Improved delivery of PLGA microparticles and microparticle-cell scaffolds in clinical needle gauges using modified viscosity formulations - Qutachi, Omar; Wright, Emma J.; Bray, Gemma; Hamid, Omar A.; Rose, Felicity R.A.J.; Shakesheff, Kevin; Delcassian, Derfogail (Elsevier, 2018)
Polymer microparticles are widely used as acellular drug delivery platforms in regenerative medicine, and have emerging potential as cellular scaffolds for therapeutic cell delivery. In the clinic, PLGA microparticles are typically administered intramuscularly or subcutaneously, with the clinician and clinical application site determining the precice needle gauge used for delivery. Here, we explored the role of needle diameter in microparticle delivery yield, and develop a modified viscosity formulation to improve microparticle delivery across a range of clinically relevent needle diameters. We have identified an optimal biocompatible formulation containing 0.25% pluronic F127 and 0.25% carboxymethyl cellulose, which can increase delivery payload to 520% across needle gauges 21-30G, and note that needle diameter impacts delivery efficacy. We use this formulation to increase the delivery yield of PLGA microparticles, and seperately, PLGA-cell scaffolds supporting viable mesenchymal stem cells (MSCs), demonstrating the first in vitro delivery of this cell scaffold system. Together, these results highlight an optimal formulation for the delivery of microparticle and microparticle-cell scaffolds, and illustrate how careful choice of delivery formulation and needle size can dramatically impact delivery payload.